Does the political will exist to bring quality-assured and affordable drugs to low- and middle-income countries?. Issue 1 (1st January 2019) - Beck, Eduard J.; Mandalia, Sundhiya; DongmoNguimfack, Boniface; Pinheiro, Eloan; 't Hoen, Ellen; Boulet, Pascale; Stover, John; Gupta, Aashta; Juneja, Sandeep; Habiyambere, Vincent; Ghys, Peter; Nunez, Cesar
ABSTRACT: Background : Increased coverage with antiretroviral therapy for people living with HIV in low- and middle-income countries has increased their life expectancy associated with non-HIV comorbidities and the need for quality-assured and affordable non-communicable diseases drugs . Funders are leaving many middle-income countries that will have to pay and provide quality-assured and affordable HIV and non-HIV drugs, including for non-communicable diseases. Objective : To estimate costs for originator and generic antiretroviral therapy as the number of people living with HIV are projected to increase between 2016 and 2026, and discuss country, regional and global factors associated with increased access to generic drugs. Methods : Based on estimates of annual demand and prices, annual cost estimates were produced for generic and originator antiretroviral drug prices in low- and middle-income countries and projected for 2016–2026. Results : Drug costs varied between US1.5 billion and US4.8 billion for generic drugs and US 8.2 billion and US16.5 billion for originator drugs between 2016 and 2026. Discussion : The global HIV response increased access to affordable generic drugs in low- and middle-income countries. Cheaper active pharmaceutical ingredients and market competition were responsible for reduced drug costs. The development and implementation of regulatory changes at country, regional and global levels, covering intellectual property rights and public health, and flexibilities in patent laws enabled prices to be reduced. These changes have not yet been applied in many low- and middle-income countries for HIV, nor for other infectious and non-communicable diseases, that lack the profile and political attention of HIV. Licensing backed up with Trade-Related Aspects of Intellectual Property Rights safeguards should become the norm to provide quality-assured and affordable drugs within competitive generic markets. Conclusion : Does the political will exist among policymakers and other stakeholders to develop and implement these country, regional and global frameworks for non-HIV drugs as they did for antiretroviral drugs?